Creativity as a “vaccine” for depressed mood: coping and divergent thinking in young adults - Alfonso-Benlliure, Vicente; Meléndez Moral, Juan Carlos (Anales de Psicología / Annals of Psychology, 2022)
The depressed mood has more and more presence in our current society. It is urgent to explore ways not only to deal with depressed mood but also to prevent it. Divergent thinking could be useful in such prevention. Certain coping strategies could mediate the relationship between divergent thinking and depressed mood. Two are the most feasible ways of connection: active problem-focused coping (like problem-solving or positive reappraisal strategies) and decreasing the odds of emotion-focused coping (like negative self-focused coping strategies). The objective of this study is to test a theoretical model that establishes the indirect relationship of divergent thinking on depressed mood. Participants were 135 subjects with ages ranging between 18 and 25 years old. The statistical analysis included structural equations modeling. The initial model led to a final model endorsed by the goodness of fit. Comparative Fit Indices for this model were: CFI = .951, GFI = .960, RMSEA = .067. This model supports a positive relationship between divergent thinking and positive reappraisal and a negative link between this kind of thinking and negative self-focused coping. Both coping strategies are connected to depressed mood. Divergent thinking can facilitate a positive reappraisal that helps to widen youngers’ repertoire of options. It can also reduce the probability of focusing on immediate and uncontrolled emotional expression, feelings of helplessness, and resignation. In one form or another, divergent thinking can promote coping strategies that can serve as a prophylaxis for hopelessness in young adults that is generally related to depressed mood.